Identification of validated substitute for Asoka (Saraca asoca (Roxb.) Willd.) by phytochemical and pharmacological evaluations - Sulaiman C. T.; Jyothi C. K.; Jinu Krishnan Unnithan G.; Prabhukumar K.M; Indira Balachandran (SpringerOpen, 2020)
Abstract Background Asoka is an important drug used in many Ayurvedic formulations. The bark of Saraca asoca (Roxb.) Willd. is the genuine source plant for Asoka. Due to diminishing availability and increasing requirement, the Ayurvedic industry is facing acute shortage of this crude drug. It is usual that traders try to deceive the consumers by tendering similar bark of other trees. The unscientific substitution may affect the quality of herbal preparations adversely. The aim of the present study is to identify a scientifically validated substitute for Asoka. Results Phytochemical and pharmacological evaluation has been carried out using plant parts of four medicinal plants viz, Saraca asoca (AB), Polyalthia longifolia (PB), Shorea robusta (SB), and Trema orientalis (TB). The results of the study showed that among the tested extracts, AB and SB showed significant dose-dependent protection against bilateral ovariectomy-induced changes in estrus cycle, uterus weights, and lipid profile. LC/MS analysis revealed the presence of active catechins in both AB and SB. Polyalthia longifolia, the common adulterant of Asoka, showed entirely different chemical and biological properties. Conclusion This study concluded the possibility of using S. robusta bark as substitute for Asoka. Graphical abstract